The Ventricular Function of the "Athlete´S Heart". Part I: Systolic Function - Francisco Javier Calderón Montero (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2018)
The knowledge of the so-called "athlete's heart"has been linked to the application of diagnostic techniques in cardiology. Perhaps, it is necessary to keep in mind that the "athlete's heart" is a physiologically "healthy" heart. The figure 1 shows the parameters that determine the mean arterial pressure. Physical exercise is the only physiological circumstance that precedes the regional metabolic demand to the control of the average blood pressure.